2015
DOI: 10.1016/j.apcata.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous γ-Fe2O3 supported palladium nanoparticles and investigation of their roles as magnetically recyclable catalysts for nitrobenzene hydrogenation

Abstract: a b s t r a c tThe mesoporous ␥-Fe 2 O 3 (maghemite) supported palladium catalysts (written as Pd/meso-␥-Fe 2 O 3 ) are synthesized using impregnation and one-step sol-gel methods and characterized by PXRD, BET, TEM, EDX, and XPS. The synthesized Pd/meso-␥-Fe 2 O 3 catalysts are applied in nitrobenzene hydrogenation reactions under 50 • C and 1 atm and their catalytic activities are compared with Pd/comm-Fe 2 O 3 , Pd/meso-SiO 2 , and Pd/meso-C catalysts, in order to study the effect of the catalyst support. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Material (catalyst) properties, such as surface area, pore structure and morphologies significantly influence the catalytic activity in heterogeneous catalytic systems. [40] Generally, higher surface area brings more active sites, leading to higher catalytic activity. The surface areas of all samples have been determined by the Brunauer-Emmett-Teller (BET) theory (Table S1).…”
Section: Materials Properties the Decisive Role Of Structurementioning
confidence: 99%
“…Material (catalyst) properties, such as surface area, pore structure and morphologies significantly influence the catalytic activity in heterogeneous catalytic systems. [40] Generally, higher surface area brings more active sites, leading to higher catalytic activity. The surface areas of all samples have been determined by the Brunauer-Emmett-Teller (BET) theory (Table S1).…”
Section: Materials Properties the Decisive Role Of Structurementioning
confidence: 99%
“…[16,20] Mesoporous materials are considered as excellent catalysts for applications requiring high surface area and large amount of active sites, due to their tunable structural properties such as surface area, pore volume, size, and nanocrystallinity. [21,22] Mesoporous titanium dioxide that combines a photoactive framework and an open porous structure is of great interest. [23] Mesoporous TiO 2 applied in the photocatalysis area has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…4 D , the pore‐size distributions of the C‐nanocasted HNTs verify that PVA molecular was fully nanocasted in the nanopore channel of HNTs by our method. In addition, it is also revealed that the as‐prepared CNRs possess two types of main mesopores at 3.9 and 9.5 nm, respectively, as calculated by the BJH method [26].…”
Section: Resultsmentioning
confidence: 99%